An interactive multimedia application for learning computer organization / Rafieq Rosian … [et al.] - Rosian, Rafieq; Kamarudin, Muhammad Fitri; Kamalrudin, Muhamad Syafiq; Hasnan, Mazliana; Othman, Zainab (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
An Interactive Multimedia Application for Learning Computer Organization Computer organization is one of the required courses for diploma and undergraduate Computer Science students. Students often faced difficulties to understand the underlying concepts in the course. Traditionally, teaching this course can be insufficient if the teaching focus is only on textbook materials. Integrating multimedia technologies in learning are increasingly used, especially for visualization of certain concept or processes. The main objective by implementing this courseware is to assists students to enhance their understanding to each chapter in this subject. Three modules of these computer organization concepts were identified: microprocessor, memory and instruction cycle. The illustration of this courseware was developed using Adobe Flash and utilized the multimedia elements including animation, text and graphics, and is designed based on a syllabus in a computer organization subject for diploma course in Universiti Teknologi MARA.